Extending UPnP for Application Interoperability in a Home Network - Kalaiselvi Arunachalam; Gopinath Ganapathy (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The Universal Plug and Play (UPnP) technology offers pervasive communication across heterogeneous devices in a home or small office network. The UPnP specifications are available for devices only to be interoperable together in a home or small office network. This paper proposes an extension of the UPnP technology for application interoperability in a home or small office network. This paper provides an UPnP Application Architecture as an extension to the existing UPnP Device Architecture. This extension enhances the feature of UPnP from device interoperability to application interoperability which enables the applications to discover, control and share data with each other in a home or small office network despite of their device type and operating system. In addition to the UPnP Application Architecture, the UPnP Application Template and UPnP Application Service Template are defined towards the development of UPnP-enabled applications that run on heterogeneous devices in a home or small office network.